Knowledge, attitude and practice of laparoscopic surgery among medical doctors in Port Harcourt, Nigeria - Ijah, Rex F. O. A.; Manuel, Amabra Dodiyi (International Surgery Journal, 2020)
Background: The use of minimal access techniques to achieve similar objectives as in open surgical procedures has witnessed a steady progress in the last two decades. The efficacy and safety of this mode of surgery has long been established. Medical doctors are not only members of the society; with their level of knowledge, their opinion is a strong mirror image of the pulse of the patients they treat. Aim of the study was to ascertain the knowledge, attitude, extent of practice, and factors affecting laparoscopic surgery among medical doctors in Port Harcourt, Nigeria. Methods: A cross sectional study of four hundred and fourteen (414) practicing medical doctors was conducted. Using stratified sampling method, self-administered semi-structured questionnaires was distributed to respondents in Port Harcourt in 2018. Data obtained was analysed using the Statistical Package for the Social Sciences (SPSS) version 20.0. Results: Knowledge of laparoscopic surgery among respondents was 89.6% (371). Three hundred and twelve respondents (75.4%) were willing to pay if such surgery is necessary and offered in Port Harcourt. Only 2.4%. of respondents asserted that laparoscopic surgery services are offered regularly in their hospital. Only 1 respondent (0.2%) was willing to pay ₦151,000.00 - 200,000.00 ($430 - $570) for commonly performed laparoscopic abdominal surgical procedures. Conclusions: Willingness to accept and knowledge of laparoscopic surgery was relatively high among medical doctors, hence a high prospect for laparoscopic surgery practice in Port Harcourt is therefore likely. The practice of laparoscopic surgery seems low and willingness to pay, even among doctors seem to be a challenge.